Peran Bank Syariah Indonesia dalam Meningkatkan Perekonomian UMKM - Sasmita Adekantari; Lailani Rukmana (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2024)
Bank Syariah Indonesia (IDX: BRIS; abbreviated as BS) means a bank in Indonesia that operates in the field of Islamic banking. This bank was inaugurated on February 1, 2021 at 13.00 WIB or coinciding with the 19th of Jumadil Akhir 1442 AH. This bank is the result of a merger between Bank Syariah mandiri, Bank BNI Syariah, and BRIsyariah. This bank is also an Islamic bank owned by HIMBARA (Association of State-Owned Banks), with its shares generally held by Bank mandiri, as a result this bank is considered to be part of the mandiri group. Bank Syariah Indonesia carries out the function of a bank to be a place to store and channel funds from the public to help development in Indonesia. The existence of a bank is also very dependent on the religion of the people. the higher the religion of the people, the higher the awareness of the people to save their money to the bank and use other services from the bank. small and medium enterprises (MSMEs) means one of the leading driving forces in the development of the manufacturing industry. the movement of the MSME sector is very important for building economic growth and employment.